2007
DOI: 10.1021/ar600035e
|View full text |Cite
|
Sign up to set email alerts
|

Nonaqueous Sol–Gel Routes to Metal Oxide Nanoparticles

Abstract: Sol-gel routes to metal oxide nanoparticles in organic solvents under exclusion of water have become a versatile alternative to aqueous methods. In comparison to the complex aqueous chemistry, nonaqueous processes offer the possibility of better understanding and controlling the reaction pathways on a molecular level, enabling the synthesis of nanomaterials with high crystallinity and well-defined and uniform particle morphologies. The organic components strongly influence the composition, size, shape, and sur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
469
0
13

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 686 publications
(484 citation statements)
references
References 61 publications
2
469
0
13
Order By: Relevance
“…Zinc oxide presents various types of one dimensional (1D) nanostructures including nanowires (NWs), nanorods (NRs), nanobelts (NBs), and nanotubes, which can be synthesized under specific growth conditions, as has been recently reviewed by Wang [7] and Niederberger [15]. Theoretical calculations have shown that ZnO piezoelectricity in 1D nanostructures is preserved with a possibility of enhanced performance due to the free boundary for volume expansion/contraction [7,16], with direct implications in the development of novel practical applications like flexible piezoelectric NRs strain sensors [17][18], piezoelectric NW FETs [19], and the use of ZnO NW arrays for the nanoscale conversion from mechanical to electric energy [1].…”
Section: Introductionmentioning
confidence: 99%
“…Zinc oxide presents various types of one dimensional (1D) nanostructures including nanowires (NWs), nanorods (NRs), nanobelts (NBs), and nanotubes, which can be synthesized under specific growth conditions, as has been recently reviewed by Wang [7] and Niederberger [15]. Theoretical calculations have shown that ZnO piezoelectricity in 1D nanostructures is preserved with a possibility of enhanced performance due to the free boundary for volume expansion/contraction [7,16], with direct implications in the development of novel practical applications like flexible piezoelectric NRs strain sensors [17][18], piezoelectric NW FETs [19], and the use of ZnO NW arrays for the nanoscale conversion from mechanical to electric energy [1].…”
Section: Introductionmentioning
confidence: 99%
“…Nanoparticles of transition metal lithium oxides with spinel-like crystal structure have been synthesized by various methods, including: laser ablation, hydrolytic sol-gel, spray drying, template synthesis, combustion synthesis, microemulsion, the Pechni method, solid state reaction, and the resorcinol-formaldehyde method [10][11][12]. Meanwhile the non hydrolitic sol-gel synthesis route [13][14], has not reported yet for lithiated oxides.…”
Section: Introductionmentioning
confidence: 99%
“…There have been many reports on the synthesis of nanostructured TiO2 using sol-gel [6][7][8], micelle [9,10], polyol, [11], sonochemical synthesis [12], hydrothermal method [13,14], and so on [3,[15][16][17]. Template-directed synthesis using titanium alkoxides as the TiO2 precursor is widely accepted as a simple and cost-effective method for the fabrication of TiO2 through the sol-gel polymerization.…”
Section: Introductionmentioning
confidence: 99%